Boundary control: the social ordering of work and family time in a high-tech corporation. - Perlow, Leslie A. (Administrative Science Quarterly, 1998)
Through a qualitative study of a software development group, I examine how managers control the hours employees work, and therefore the temporal boundary between employees' work and life outside of work. Analysis of field data shows that managers use three types of techniques to exert boundary control over “knowledge workers”: (1) imposing demands, by setting meetings, reviews, and internal deadlines, controlling vacations, and requesting extra work; (2) monitoring employees, by standing over them, checking up on them, and observing them; and (3) modeling the behavior they want employees to exhibit. Employees either accept or resist managers' boundary control; those who resist are penalized by the reward system, even when they devise creative ways to schedule and complete their work. Many employees are married, and the demands of their work have consequences for their spouses. Spouses' reactions to the demands that ultimately affect them further influence how employees respond to boundary control. These findings contribute to a theory of boundary control and carry practical implications for resolving work-family conflicts in our society. Reprinted by permission of the publisher.